Autobiographical memory transmission with phenomenological change over time - Kara, Gönenç. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
Previous studies have revealed some differences for phenomenology between imagined and perceived events. In the present study, phenomenology for autobiographical memory of someone else was explored in parallel with own autobiographical memories. University students (N = 68) were invited to a laboratory for two interview sessions one week apart from each other in order to also discover the effect of retelling over time. To-be-transmitted memory with either positive or negative emotions was presented to each participant either through video or transcript. Participants were asked to report phenomenological ratings to one of their most important memories as well as to the presented transmitted memory after they were asked to narrate these memories. Results showed that the time factor was important for both own and transmitted memories especially with regard to some measures of belief in accuracy which were found to be lower in the second session. Some sensory components were also found to lose their strengths over time for transmitted memories. Transmitted memory with negative emotions had higher ratings for feelings of living than transmitted memory with positive emotions while the latter had higher ratings for belief in accuracy. There was also some evidence for the impact of presentation type on belief in accuracy in that memory transmission through video returned higher ratings than memory transmission through transcript. The results show that phenomenology for autobiographical memory of someone else could depend on emotional valence as well as on how it is presented and when that phenomenology is measured over time.
Keywords: Autobiographical memory.; Memory -- Social aspects.; Collective memory